O trabalho doméstico não remunerado na publicidade: as estruturas de sentimento da marca “Mr. Músculo” - Nunes, Lucas da Silva (2024)
This research aims to question the way in which the relationships between gender and unpaid domestic work were constructed in 8 audiovisual advertisements from the brand Mr. Muscle. To do so, it uses the episteme of Cultural Studies. We pose as a research problem: How were the relationships between gender and unpaid domestic work constructed in the campaigns of the company Mr. Muscle? The general objective is to investigate the meanings produced by the Mr. Muscle brand's audiovisual advertisements, relating them to conceptions of gender and unpaid domestic work present in lived culture and their representations in advertising pieces, in order to identify elements that show continuities and/or ruptures regarding the role of women and men within these spaces. As specific objectives, we intend to: contextualize unpaid domestic work within the scope of lived culture; identify, through the elements of lived culture present in the discourse of the analyzed audiovisuals, what were the representations of gender and their roles within the domestic space; point out what are the continuities, ruptures, and agendas activated in the brand's discourse, through the structures of feeling. For this, we chose to develop our own methodological approach, based on the perspective of Cultural (Media) Analysis and the analytical instrument of textual analysis by Cassetti and Chio (1999). We identified that the brand underwent a repositioning over the years, initially with a more traditional advertising discourse that reinforced gender hierarchy and segregation, highlighting unpaid domestic work. However, over time, it distanced itself from this discourse by including women in the workforce and men in the domestic space, reaching 2019 with the agenda of sharing activities. The analysis of the brand's audiovisuals revealed that it distanced itself from older meanings about gender roles, although it still retains characteristics of discrimination, such as the exaltation of heteronormative couples and the limited representation of social classes in its campaigns. The research also revealed that the brand's structures of feeling are not static, but are constantly evolving. We also point out the hybridization of structures of feeling, identified as a marketing practice to include progressive agendas in advertising. Through our analysis process, we were able to conclude that there was a repositioning of the brand over the years. Initially, there was a greater affinity with "traditional advertising models," reintroducing meanings about the hierarchy and segregation between genders, regarding unpaid domestic work. However, over time, it distanced itself from this discourse by bringing the inclusion of women in the workforce and men into the domestic space into its texts, reaching 2019 with the agenda of sharing activities.